Enabling biomass combustion and co-firing through the use of Lignocol. (1st January 2018) - Rover, Marjorie; Smith, Ryan; Brown, Robert C.
Graphical abstract: Highlights: Lignocol is a solid fuel derived from fast pyrolysis of lignocellulose. Lignocol can be co-fired with coal without loss of boiler capacity. Sulfur and nitrogen emissions are significantly reduced compared to coal. Lignocol has comparable or higher heating values as commercially significant coals. Abstract: We have developed a biomass-derived solid fuel, referred to as Lignocol, that can reduce sulfur and nitrogen emissions from coal-fired power plants without suffering the ash fouling and loss of boiler capacity usually associated with co-firing biomass. To produce Lignocol, lignocellulosic biomass was pyrolyzed to vapors that were condensed as distinct fractions of bio-oil. The heavy ends of bio-oil, consisting primarily of anhydrosugars from holocellulose and phenolics from lignin in the biomass, was subjected to a water extraction to produce separate streams of water-insoluble phenolics and water-soluble sugars. The phenolics were cured at 105–220 °C to evaporate water and expedite cross-linking reactions that solidified the phenolic liquid into Lignocol. The higher heating value (HHV) and particle density of Lignocol were similar to several commercially significant coals in the United States while the nitrogen and sulfur contents were only 0.26 wt% and 0.02 wt%, respectively, much lower than typically found in coal. The ash content of Lignocol was less than 0.5 wt% compared to 3–10 wt% for coals. Lignocol was structurally stable in the presence of water and only leached 8.52 ppm and 9.03 ppm of aromatics at pH 4.2 and 5.0, respectively. Lignocol was combusted at 650 °C in a 100 g/h fluidized bed reactor to determine feeding characteristics. Neither melting in the feeder system nor agglomeration in the reactor were observed. Based on these observations, Lignocol has excellent prospects for high levels of co-firing with coal in power plants and replacing wood pellets in dedicated biomass-firing while avoiding the usual challenges of burning biomass.